Never over - Gilmore, Clare (St. Martin's Griffin, 2025)
"A swoony second-chance romance where facing the one who broke your heart could be the thing that makes your dream come true. Twenty-five-year-old Paige Lancaster is one contract away from earning a living doing her favorite thing in the world: writing songs. But when a music industry professional suggests she might be holding back with her lyrics to lessen the heartbreak of an old flame, Paige doubts if her music is ready to be heard. In a rare, impulsive move, Paige reaches out to Liam Bishop after four years of no-contact to ask him for a small favor: date her, and then re-break her heart, all so she can remember what those big, songworthy emotions felt like. And since Liam is the one who first set Paige on this career path, he hesitantly agrees. Across two months of Liam's summer work travel, the exes are forced to share hotel beds, rehash the past, and date in the present, all while navigating the building attraction between them they both swore was the one line of their agreement they wouldn't cross. But when it becomes near impossible not to act on their rippling chemistry, and as ever intensifying feelings blur reality with what's driven by the music, Paige and Liam will both have to decide which is more important: art for the sake of it, or love over everything"--